Past tree range dynamics in the Iberian Peninsula inferred through phylogeography and palaeodistribution modelling: A review - Rodríguez-Sánchez, Francisco; Hampe, Arndt; Jordano, Pedro; Arroyo, Juan (Review of Palaeobotany and Palynology, 2010)
The forests in the Iberian Peninsula have been strongly inﬂuenced by past climatic changes, but reconstructing their historical distributions and dynamics is very difﬁcult due to the complex climatic characteristics and relief of the region. Research disciplines such as phylogeography and species distribution modelling can describe the past range dynamics of individual tree species in relatively great detail and help elucidate how these species have reacted to climatic changes. Here we review phylogeographical and modelling studies from species representative of the major Iberian forest types and attempt to extract general trends from the diversity of individual species histories in the Peninsula. To date most studies focus on geographical range dynamics during the Pleistocene, but an increasing body of evidence shows that some species have also retained the genetic imprints of much more ancient processes. Many widespread Iberian species show a deep and often remarkably clear-cut divide between populations from the Mediterranean and from the Atlantic regions of the Iberian Peninsula, suggesting that both areas have independently sustained viable populations over extended periods. In fact, phylogeographical studies commonly ﬁnd that species had several glacial refugia across the Iberian Peninsula. On the other hand, distribution models help identifying further suitable areas that could have sustained so far undetected refugia. Such studies are of interest for species conservation, because refugium populations are high-priority targets due to their longterm persistence and unique evolutionary trajectory. Overall, we conclude that palaeoecology, phylogeography and species distribution modelling have a great potential to inform each other because of their complementary perspectives and results. A true integration of these approaches is therefore fundamental for further progress in our understanding of past Iberian environments and the organisms they harboured.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: genetic diversity; glacial refugia; hindcasting; palaeobiogeography; Spain; species distribution modelling

A coastal reservoir of biodiversity for Upper Pleistocene human populations: palaeoecological investigations in Gorham's Cave (Gibraltar) in the context of the Iberian Peninsula - Carrión, J S; Finlayson, C; Fernández, S; Finlayson, G; Allué, E; López-Sáez, J A; López-García, P; Gil-Romera, G; Bailey, G; González-Sampériz, P; Carrion, J; Fernández, S; et al. (Quaternary Science Reviews, 2008)
Palaeobotanical (pollen, charcoal) data from Gorham’s Cave reveals a diversified landscape in the Gibraltar region during the Middle (c. 32 560–23 780 year BP) and Upper Palaeolithic (c. 18 440–10 880 BP). Inferred vegetation types include oak, pine, juniper, and mixed woodlands and savannahs, grasslands with heaths, heliophytic matorrals, phreatophytic formations (e.g. riverine forests, wetlands), and thermomediterranean coastal scrub. A revision of palaeoecological data suggests that patches of trees persisted even in northern and continental territories of the Iberian Peninsula during the cold stages of OIS3 and OIS2. However, a southern Mediterranean coastal shelf extending from Gibraltar to Málaga, and probably further north up to Murcia, was unique in its combination of thermo-, meso-, and supramediterranean plant and animal species. Given the composition of these assemblages, this shelf and its adjacent mountains represented a crucial reservoir of biodiversity during the Upper Pleistocene. It is within this physiographically complex context with its diversity of resources where the last Neanderthals extraordinarily survived until c. 24 000 BP, that is over 10 000 years later than the disappearance of Neanderthals from elsewhere in temperate Europe.
Keywords: climatic fluctuations (voyant); Gibraltar; glacial refugia; Mediterranean; Quercus

Molecular and palaeoecological evidence for multiple glacial refugia for evergreen oaks on the Iberian Peninsula - López de Heredia, U.; Carrión, J. S.; JIMÉNEZ, P.; COLLADA, C.; Gil, L. (Journal of Biogeography, 2007)
Aim A multiple glacial refugia hypothesis for Mediterranean plant species was tested with the evergreen Quercus complex (Quercus suber L., Quercus ilex L. and Quercus coccifera L.) from the Iberian Peninsula, using molecular and palaeobotanical data. Location The Iberian Peninsula, which is an ecologically and physiographically complex area located on the western edge of the Mediterranean Basin. Methods We sampled 1522 individuals from 164 populations of Q. suber, Q. ilex and Q. coccifera. A review of the recent literature on fossil pollen and charcoal records and a nested clade analysis on chloroplast DNA polymerase chain reaction-restriction fragment length polymorphism was carried out to infer demographic and historical processes. Results The analysis indicates at least one glacial refugium for Q. suber in southwestern Iberia. Extensive introgression of Q. suber with Q. ilex indicates several potential refugia in eastern Iberia. Past fragmentation was followed by a restricted range ﬂow/range expansion, suggesting multiple refugia for Q. ilex–Q. coccifera elsewhere in central and northern Iberia and multiple areas of secondary contact. This ﬁnding is consistent with fossil records. Main conclusions The predicted multiple refugia during glacial periods indicates the existence of secondary post-glaciation contact areas. These areas contained complex diversity patterns resulting mainly from range expansions followed by isolation by distance. To a lesser degree, traces of restricted and longdistance dispersal were also found.
Keywords: cpDNA PCR-RFLPs; evergreen Quercus; fossil pollen; glacial refugia; iberian peninsula; introgression; nested clade analysis; oaks; phylogeography

La diversitá cloroplastica delle querce italiane: evidenze di una maggiore ricchezza genetica nelle popolazioni meridionali e insulari - Fineschi, S; Vendramin, G G (iForest - Biogeosciences and Forestry, 2004)
Results of the analysis of non-coding regions of the chloroplast genome in Italian population of deciduous oaks (subgenus Quercus) and holm oak (subgenus Scleropyllodris) are reported. Deciduous oak revealed the occurrence of six chloroplast haplotypes, differently distributed in the single geographic areas (northern, central, and southern Italy, and major islands). Moreover, most of the present Italian oak populations seems to derive from two major refugia, located in Sicily and in the Balkans, respectively. The most likely migration dynamics from the refugia towards the central and northern part of the peninsula are discussed. Migration pathways resulted to have been different in the various geographic areas. The presence of an endemic haplotype in Sardinia and Corsica was considered of particular interest. In Italian holm oak populations eight haplotypes were detected, six of them in Sicily. Five out of six Sicilian haplotypes resulted to be endemic. The Italian peninsula was colonized by two major haplotypes, one of them originating from Sicily. Results on deciduous oaks and holm oak in Italy highlight the important role played by the populations from the south and from the major islands in the colonization the Italian peninsula after the last ice age.
Keywords: Chloroplastic Diversity; colonization; conservation; glacial refugia; phylogeography; Quercus

La diversitá cloroplastica delle querce italiane: evidenze di una maggiore ricchezza genetica nelle popolazioni meridionali e insulari - Fineschi, S.; Vendramin, G. G. (iForest - Biogeosciences and Forestry, 2004)
Results of the analysis of non-coding regions of the chloroplast genome in Italian population of deciduous oaks (subgenus Quercus) and holm oak (subgenus Scleropyllodris) are reported. Deciduous oak revealed the occurrence of six chloroplast haplotypes, differently distributed in the single geographic areas (northern, central, and southern Italy, and major islands). Moreover, most of the present Italian oak populations seems to derive from two major refugia, located in Sicily and in the Balkans, respectively. The most likely migration dynamics from the refugia towards the central and northern part of the peninsula are discussed. Migration pathways resulted to have been different in the various geographic areas. The presence of an endemic haplotype in Sardinia and Corsica was considered of particular interest. In Italian holm oak populations eight haplotypes were detected, six of them in Sicily. Five out of six Sicilian haplotypes resulted to be endemic. The Italian peninsula was colonized by two major haplotypes, one of them originating from Sicily. Results on deciduous oaks and holm oak in Italy highlight the important role played by the populations from the south and from the major islands in the colonization the Italian peninsula after the last ice age.
The following values have no corresponding Zotero field: pub-location: (1) CNR Istituto per la Protezione delle Piante, via Madonna del Piano, Edificio E, 50019 Sesto Fiorentino, Firenze; (2) CNR Istituto di Genetica Vegetale, sezione di Firenze, via Madonna del Piano, Edificio D, 50019 Sesto Fiorentino, Firenze publisher: SISEF - Italian Society of Silviculture and Forest Ecology
Keywords: Chloroplastic Diversity; colonization; conservation; glacial refugia; phylogeography; Quercus

Differential success in northwards range expansion between ecotypes of the marble gallwasp Andricus kollari: a tale of two lifecycles - Stone, G.; Atkinson, R.; Rokas, A.; Csoka, G.; Nieves-Aldrey, J. L.; Csoka, G.; Nieves-Aldrey, J. L. (MOLECULAR ECOLOGY, 2001)
The Marble gallwasp Andricus kollari has a native range divided into two geographically separated lifecycles. In Eastern Europe and Turkey, the lifecycle involves a sexual generation on Turkey oak, Quercus cerris, while in Iberia and North Africa the sexual generation host is cork oak, Q. suber. Over the last 500 years, A. kollari has expanded its range into northern Europe, following human planting of Q. cem's from Italy and the Balkans. We ask: (i) what is the genetic relationship between eastern and western distributions of Andricus kollari? Can we determine which lifecycle is ancestral, and how long ago they diverged? (ii) To what extent have eastern and western native ranges contributed to northwards range expansion? (iii) Is there any evidence for hybridization between the two life cycle types? We present analyses of allozyme data for 13 polymorphic loci and of sequence variation for a 433 bp fragment of the mitochondrial cytochrome b gene. These show: (i) that four haplotype lineages (one in Spain, two in Hungary/Italy and one in Turkey) diverged more or less simultaneously between 1 and 2 million years ago, suggesting the existence of at least four refuges through recent ice age cycles. Our data cannot resolve which lifecycle type is ancestral. (ii) Populations north of putative refuges are divided into two sets. Populations in south-west France are allied to Spain, while ail remaining populations in northern Europe have been colonized from Italy and the Balkans. (iii) The transition from one race to another in south-west France is marked by abrupt transitions in the frequency of refuge-specific private alleles and corresponds closely to the northern limit of the distribution of cork oak. Although hybrids were detected in north-west France, none were detected where the two lifecycles meet in south-western France. The biology of oak gallwasps predicts that any hybrid zone will be narrow and limited to regions where Q. cem's and Q. suber meet. Our data suggest that eastern and western A. kollari are effectively separate species.
From Duplicate 2 (Differential success in northwards range expansion between ecotypes of the marble gallwasp Andricus kollari: a tale of two lifecycles - Stone, G; Atkinson, R; Rokas, A; Csoka, G; Nieves-Aldrey, J L)From Duplicate 2 (Differential success in northwards range expansion between ecotypes of the marble gallwasp Andricus kollari: a tale of two lifecycles - Stone, G; Atkinson, R; Rokas, A; Csoka, G; Nieves-Aldrey, J L)The following values have no corresponding Zotero field: pub-location: COMMERCE PLACE, 350 MAIN ST, MALDEN 02148, MA USA publisher: WILEY-BLACKWELL accession-num: 11298986
Keywords: Alleles; Andricus; Animals; Base Sequence; Cellulose Acetate; Cytochrome b Group; Cytochrome b Group: chemistry; Cytochrome b Group: genetics; DNA; Electrophoresis; Environment; EUROPE; Evolution; Female; gallwasp; Genetic Variation; Genetic Variation: physiology; glacial refugia; host race; Hymenoptera; Hymenoptera: genetics; Hymenoptera: growth & development; Hymenoptera: physiology; invasion; Life Cycle Stages; Mitochondrial; Mitochondrial: chemistry; Mitochondrial: isolation & purification; Molecular; Molecular Sequence Data; Parthenogenesis; phylogeny; Polymerase Chain Reaction; range expansion; Sequence Alignment; Sequence Analysis

Differential success in northwards range expansion between ecotypes of the marble gallwasp Andricus kollari: a tale of two lifecycles - Stone, G; Atkinson, R; Rokas, A; Csoka, G; Nieves-Aldrey, J L; Csoka, G; Nieves-Aldrey, J L (MOLECULAR ECOLOGY, 2001)
The Marble gallwasp Andricus kollari has a native range divided into two geographically separated lifecycles. In Eastern Europe and Turkey, the lifecycle involves a sexual generation on Turkey oak, Quercus cerris, while in Iberia and North Africa the sexual generation host is cork oak, Q. suber. Over the last 500 years, A. kollari has expanded its range into northern Europe, following human planting of Q. cem's from Italy and the Balkans. We ask: (i) what is the genetic relationship between eastern and western distributions of Andricus kollari? Can we determine which lifecycle is ancestral, and how long ago they diverged? (ii) To what extent have eastern and western native ranges contributed to northwards range expansion? (iii) Is there any evidence for hybridization between the two life cycle types? We present analyses of allozyme data for 13 polymorphic loci and of sequence variation for a 433 bp fragment of the mitochondrial cytochrome b gene. These show: (i) that four haplotype lineages (one in Spain, two in Hungary/Italy and one in Turkey) diverged more or less simultaneously between 1 and 2 million years ago, suggesting the existence of at least four refuges through recent ice age cycles. Our data cannot resolve which lifecycle type is ancestral. (ii) Populations north of putative refuges are divided into two sets. Populations in south-west France are allied to Spain, while ail remaining populations in northern Europe have been colonized from Italy and the Balkans. (iii) The transition from one race to another in south-west France is marked by abrupt transitions in the frequency of refuge-specific private alleles and corresponds closely to the northern limit of the distribution of cork oak. Although hybrids were detected in north-west France, none were detected where the two lifecycles meet in south-western France. The biology of oak gallwasps predicts that any hybrid zone will be narrow and limited to regions where Q. cem's and Q. suber meet. Our data suggest that eastern and western A. kollari are effectively separate species.
From Duplicate 2 (Differential success in northwards range expansion between ecotypes of the marble gallwasp Andricus kollari: a tale of two lifecycles - Stone, G; Atkinson, R; Rokas, A; Csoka, G; Nieves-Aldrey, J L)
Keywords: Alleles; Andricus; Animals; Base Sequence; Cellulose Acetate; Cytochrome b Group; Cytochrome b Group: chemistry; Cytochrome b Group: genetics; DNA; Electrophoresis; Environment; EUROPE; Evolution; Female; gallwasp; Genetic Variation; Genetic Variation: physiology; glacial refugia; host race; Hymenoptera; Hymenoptera: genetics; Hymenoptera: growth & development; Hymenoptera: physiology; invasion; Life Cycle Stages; Mitochondrial; Mitochondrial: chemistry; Mitochondrial: isolation & purification; Molecular; Molecular Sequence Data; Parthenogenesis; phylogeny; Polymerase Chain Reaction; range expansion; Sequence Alignment; Sequence Analysis